End effects in low aspect ratio Taylor–Couette flow. (20th March 2023) - Wiswell, H.; Snow, B.; Tricouros, F. A.; Smits, A. J.; Van Buren, T.
Abstract : Taylor–Couette flow with a low aspect ratio cylinder suffers from end effects due to the finite-span of the gap between the cylinder sides and the secondary flow in the region below the inner cylinder. We experimentally explore these end effects by varying the cylinder aspect ratio between 6.67 and 40 for a range of wall gap widths and bottom gap heights. For these geometries, end effects (i.e. non-ideal Taylor–Couette flow) can be substantial due to both features of the finite-span and the bottom secondary flow. In some cases, the finite-span effects extended between 20% and 30% of the way into the Taylor–Couette flow region, and the secondary flow at the bottom accounted for nearly half of the total measured torque. By taking these effects into consideration, our high aspect ratio results agreed well with those obtained by Taylor (Taylor 1936 Proc. R. Soc. Lond. A 157, 546–564. (doi:10.1098/rspa.1936.0215 )) at considerably higher aspect ratios. This article is part of the theme issue 'Taylor–Couette and related flows on the centennial of Taylor's seminal Philosophical Transactions paper (part 1)'.